(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
In marketplace, it is normally observed that the utility of some items increases with time. For instance, in breweries, the value of some stocked wine increases with time. In farms, the quantity or weight of fish, fast growing animals including broilers, sheep, and so on, increase with time. These phenomena are termed amelioration. In this paper therefore, we study an inventory model that determines the optimal replenishment decision for ameliorating items with stock dependent demand where the holding cost and the rate of amelioration are considered constants. The concept of differential and integral calculus was used to optimize the cost function to obtain numerical examples that illustrate the effects of parameter changes on the decision variables and to find the optimum number of replenishments. The model could be used by the organizations that deal with the relevant items.